Oral health status in Ecuador - Parise-Vasco, Juan Marcos (2020)
In Ecuador, there is a high prevalence and incidence of different oral pathologies, this scenario is similar in several countries in the region. Oral diseases constitute a Public Health issue, since they involve a high investment in their management and control. Thus, an emphasis in preventive activities has been placed to improve the impact of oral diseases. Several measures have been taken by the Ecuadorian government to reduce the incidence of dental caries, including massive prevention programmes. For instance, fluoridation of food and water, school teaching of right tooth brushing techniques and dental floss use, early detection of bacterial plaque, delivery of educational talks, and sealant placement on occlusal surfaces of permanent teeth in schoolchildren from deprived urban and rural populations. Nevertheless, these strategies have not been monitored, evaluated or reported in order to understand their success in improving the Oral Health status of our country.